2016
DOI: 10.1038/gim.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Carrier screening in the era of expanding genetic technology

Abstract: In a primarily Jewish population, NGS reveals a larger number of pathogenic variants and provides individuals with valuable information for family planning.Genet Med 18 12, 1214-1217.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Our findings are consistent with the expectation and previous reports that increasing the number of genes in a panel results in an increase in the number of individuals identified as carriers for a single genetic condition and for individuals identified as carriers for multiple genetic conditions (Arjunan et al, ; Baskovich et al, ; Haque et al, ; Lazarin et al, ; Terhaar et al, ). Our pan‐ethnic expanded carrier screening panel of 87 genes increased the carrier detection rate among AJ individuals by approximately 50% compared with the 18‐gene AJ panel and by approximately 100% compared with the nine ACMG genes recommended for AJ carrier screening.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the expectation and previous reports that increasing the number of genes in a panel results in an increase in the number of individuals identified as carriers for a single genetic condition and for individuals identified as carriers for multiple genetic conditions (Arjunan et al, ; Baskovich et al, ; Haque et al, ; Lazarin et al, ; Terhaar et al, ). Our pan‐ethnic expanded carrier screening panel of 87 genes increased the carrier detection rate among AJ individuals by approximately 50% compared with the 18‐gene AJ panel and by approximately 100% compared with the nine ACMG genes recommended for AJ carrier screening.…”
Section: Discussionsupporting
confidence: 93%
“…Lazarin et al () assessed the carrier frequencies for more than 400 Mendelian variants in an expanded carrier screening panel for a pan‐ethnic population, with results stratified by ethnicity, but did not have carrier frequency data obtained directly from a cohort of patients tested by a corresponding AJ panel. A study by the Center for Jewish Genetics tested 506 individuals, approximately 85% of whom identified as AJ, and compared next‐generation sequencing (NGS)‐based expanded carrier screening results with those obtained by targeted genotyping for SMN1 and founder mutations in 18 genes causing AJ genetic disorders (Arjunan, Litwack, Collins, & Charrow, ). In this study, 288 (57%) of individuals were identified as carriers for at least one disorder by NGS and 52 of these individuals (18% of carriers) would not have been identified without the expanded NGS panel.…”
Section: Introductionmentioning
confidence: 99%
“…The high-throughput ability of NGS has been successfully used to diagnose LSDs [ 54 , 55 , 56 , 57 , 58 , 59 ], both in the form of exome and targeted sequencing. This is particularly useful when applied to specific diagnostic contexts, including carrier screening studies in high-risk populations (e.g., the Ashkenazi Jewish population) [ 60 , 61 ], prenatal diagnosis [ 62 ], unsolved cases where traditional molecular diagnostic approaches have failed [ 63 ], unclear or suspected LSD cases [ 64 , 65 ], as well as in defining genotype–phenotype correlations [ 66 ] or to find out genetic disease modifiers [ 67 ]. More interesting is the use of NGS to differentiate genetically heterogeneous diseases with overlapping clinical phenotypes, such as Pompe disease, limb-girdle muscular dystrophies [ 68 , 69 ], and Gangliosidosis [ 70 ], or to investigate mosaic conditions [ 71 , 72 ].…”
Section: Opportunities and Challenges For Genomics In Lsdsmentioning
confidence: 99%
“…Currently, guidelines established by the American College of Medical Genetics and Genomics and the American College of Obstetricians and Gynecologists recommend screening for 4-9 conditions in individuals of Ashkenazi Jewish descent. (16) The most advanced genetic testing technologies comprise a greater number of disorders than the previous recommendations, with an approximate number of 19, including TSD. (16) Prenatal screening for TSD was introduced in 1971 in the U.S. and throughout history its application has been directed only at Ashkenazi Jewish populations.…”
Section: Diagnosismentioning
confidence: 99%
“…(16) The most advanced genetic testing technologies comprise a greater number of disorders than the previous recommendations, with an approximate number of 19, including TSD. (16) Prenatal screening for TSD was introduced in 1971 in the U.S. and throughout history its application has been directed only at Ashkenazi Jewish populations. (9,13,17) Between 2006 and early 2011, the median number of tests per month was 2 900, with an annual rate of 35 000; the analytical sensitivity and specificity for U.S. participants were 97.2% and 99.8%, respectively.…”
Section: Diagnosismentioning
confidence: 99%